Le Carême et le Ramadan : recréer le corps. Un cas libanais - Aïda Kanafani-Zahar (Revue des Mondes Musulmans et de la Méditerranée)
To bring into accord the body with the requirements of the sacred in order to enhance a religious fervour of great intensity is the aim of Lent and of Ramadan. New norms are set. They draw their legitimacy from a corpus of symbols based, for Lent, on the colour and taste of food, the desire for nature, voluntary privations, and for Ramadan, on the disruption on the food rhythm. In the Christian and Muslim fasts, as they are experienced in Hsoun, a village in Mount Lebanon, the relationship between the food time and the piety time is at its highest.